(3EHQGR dWGFa GdZhGeV hEMQGR UfGYI GdaQGFVs - (3TgGH GdOjf CHi GdYHGS CMeO Hf QLH Hf WjHZG Hf GdeLOi GdbGgQi GdTGaYjs; (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3hHYO , agPG eNJUQ ef cJGHi GdehShe HGdcGai ai ehGQjK GdCeI CdN s
(3BNQgG (B:s
(3aEPG bdJ GdSgGe cGf Pdc ChLR ai eYQaI GdCfUHGA YfO GdbSeI ChGdeHGjYI Ch GdELGRI hfMh Pdc s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
Keywords: (3GdQjGVjGJs